2023
DOI: 10.18178/ijiet.2023.13.2.1799
|View full text |Cite
|
Sign up to set email alerts
|

Massive Open Online Courses (MOOCs) in Higher Education: A Bibliometric Analysis (2012-2022)

Abstract: Nowadays, Massive Open Online Courses (MOOCs) have become an increasingly popular online learning environment. However, existing studies did not offer comprehensive findings and deeper exploration of MOOCs. This study presents a bibliometric review of 3201 studies up to 2022 from the Scopus database. Although the first study was conducted in 2012, most of the studies were published in 2021. The literature on MOOCs is growing significantly and this pattern is expected to increase in 2022 and beyond. The most ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…As a result, it can significantly contribute to education and improve the quality of learning in universities. Previous research by Irwanto et al (2023) also showed increased publications over the same period. Therefore, research on MOOCs in LMS learning requires further efforts from researchers to maintain consistency in number of publications and develop new methods and techniques in studying this topic.…”
Section: Discussionmentioning
confidence: 55%
“…As a result, it can significantly contribute to education and improve the quality of learning in universities. Previous research by Irwanto et al (2023) also showed increased publications over the same period. Therefore, research on MOOCs in LMS learning requires further efforts from researchers to maintain consistency in number of publications and develop new methods and techniques in studying this topic.…”
Section: Discussionmentioning
confidence: 55%
“…online courses [7][8][9], STEM Education [10,11], big data [12], professional development teacher [13], innovation in education [14], and industry 4.0 and education [15]. However, research on computational mapping of bibliometric analysis of published data in the field of science process skill which has been carried out specifically to determine the development of the research has not been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from student learning experiences, existing literature has also observed the impact of implementing mobile apps on motivation. Mobile learning applications were effective in increasing students' motivation in studying chemistry [28].…”
Section: Introductionmentioning
confidence: 99%